Physical, chemical, and biological changes in the rhizosphere and nutrient availability - Fageria, N.K; Stone, L.F (Journal of plant nutrition, 2006)
The rhizosphere is the soil zone adjacent to plant roots which is physically, chemically, and biologically different from bulk or non-rhizosphere soil. Adaptative mechanisms of plants influence physical (temperature, water availability, and structure), chemical pH, redox potential, nutrient concentration, root exudates, aluminum (Al) detoxification and allelopathy, and biological properties (microbial association) in the rhizosphere. These changes affect nutrient solubility, transport, and uptake and ultimately plant growth. Major rhizosphere changes are synthesized and their influence on nutrient availability is discussed. In the last decade, significant progress has been made in understanding the rhizosphere environment and nutrient availability. However, the subject matter is very complex and more research is needed to understand the interaction between the plant, the rhizosphere environment, and nutrient availability.